Ultrahigh-field imaging (7 Tesla) in DNET: Unmasking microstructural imaging characteristics – A case report - Marta Calvo-Imirizaldu; Daniele Botta; Margitta Seeck; Jan Novy; Jose Federico Ojeda Esparza; Aikaterini Fitsiori; Corrado Santarosa; Kevin Battistini; Karl-Olof Lövblad; Felix T. Kurz (Epilepsy & Behavior Reports)
Commercial ultrahigh-field 7 Tesla (T) MRI has been approved for clinical brain imaging, including applications in epilepsy and brain tumors. Increasing magnetic field strength offers significant advantages over lower-field MRI due to improved spatial resolution, signal-to-noise ratio, and contrast-to-noise ratio. These improvements provide better anatomical delineation and gray-white matter tissue-contrast differentiation.We present a case of a presumed dysembryoplastic neuroepithelial tumor (DNET) imaged at 7 T MRI of the second generation, which revealed an unprecedented level of detail of the complex and intricate tumor architecture. Insights of its different components correlate closely with its known histopathological features. These tumors are unique among low-grade neoplasms due to their distinct clinical presentation, imaging features, and histopathological architecture. DNETs are rare, typically occurring in young patients with refractory epilepsy, and are classified by their well-defined histological subtypes. We review the various MRI patterns of DNET, which have been shown to correlate with histological subtypes and the extent of the epileptogenic zone.Complete tumor resection is essential for long-term control and recurrence prevention, emphasizing the importance of precise preoperative visualization of the tumor and its surrounding tissue. In this case, 7 T images demonstrated superior lesion conspicuity and clearer boundaries, highlighting the advantages of ultrahigh-field MRI in defining the full extent of the lesion. Although 7 T MRI is not yet widely available, it has started to gain an important role in the management of epilepsy, particularly for cases requiring detailed structural analysis.